The Role of the Binjai Muhammadiyah Regional Leadership Elementary Education Council as Supervisory at MTs Aisyiyah - Istifa Kemal; Indra Prasetia; Akrim Akrim; Aswita Utami (RIRAI Publisher, 2023)
Identification of the problems in this study are (1) The role of the Majelis Dikdasmen Binjai in the development of institutions at MTs Aisyiyah Binjai, (2) The Majelis Dikdasmen Binjai as the Supervisory Board at MTs Aisyiyah. The research method used in this research is a case study qualitative research. There were 7 research subjects. Research using qualitative methods. Data collection was in the form of interview guidelines, observations, and recording devices to facilitate data collection related to the Role of the Majelis Dikdasmen Binjai as the Supervisory Board at MTs Aisyiyah Binjai. The results of the research show that the role of a Supervisory Board at MTs Aisyiyah has carried out its duties and functions in the development of institutions at MTs Aisyiyah. Carry out supervision of the proposal, appointment and dismissal of school principals, teachers and employees. Plan and approve the Madrasah budget and income. The role of Majelis Dikdasmen Binjai has carried out its role as a supervisory body at MTs Aisyiyah Binjai well.